Respuesta :

Answer:

x=0

Step-by-step explanation:

(x^2 + 4x) - 2x = x^2 +x

Combine like terms

x^2 +2x = x^2 +x

Subtract x^2 from each side

2x =x

Subtract x from each

2x-x = x-x

x = 0

Answer:

[tex]x=0[/tex]

Step-by-step explanation:

[tex]x^2+4x-2x=x^2+x[/tex]

Combine like terms.

[tex]x^2+2x=x^2+x[/tex]

Add [tex]-x^2[/tex] and [tex]-2x[/tex] on both sides.

[tex]x^2+2x-x^2-2x=x^2+x-x^2-2x[/tex]

[tex]0=x-2x[/tex]

[tex]0=-1x[/tex]

Divide both sides by [tex]-1[/tex].

[tex]\frac{0}{-1} =\frac{-1x}{-1}[/tex]

[tex]0=x[/tex]